Inovasi Pembelajaran Oleh Guru Di Jember Pada Masa Pandemi Covid 19 - Tiara, Tiara; Herlindawati, Dwi; Kantun, Sri (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This study aims to analyze teacher innovation in learning in the era of the co-19 pandemic. The research method uses qualitative research with a phenomenological approach. The research was conducted in Jember district with an economics teacher at the high school level as the subject. The data presented in this study is in the form of an overview of learning innovations carried out by teachers during the Covid-19 pandemic seen from six dimensions: (1) learning objectives, (2) teacher’s role (s) (3) students' role(s), (4) ICT used, (5) connectedness, and (6) multiplicity of learning outcomes exhibited. The results of the research show that the learning objectives dimension is in the some new elements level category, the teacher's role dimension in the learning process is in the emergent level category, the student's role dimension in the learning process is in the some new elements level category, the ICT dimension used in learning effectiveness and learning was found to be in the emergent level category, the connectedness dimension of the learning process was found to be in the some new elements level category, the diversity dimension of evaluation of learning results used by teachers was in the some new elements level category.